Assessment and comparison of anemia of chronic disease in healthy subjects and chronic periodontitis patients: A clinical and hematological study - Rajashri A Kolte; Abhay P Kolte; Neha M Deshpande (Wolters Kluwer Medknow Publications, 2014)
Background: Bacteremia is associated with periodontal diseases whose extent is related to the severity of inflammation in periodontal tissues. The purpose of this study was to assess and compare the various blood parameters in healthy subjects and severe chronic periodontitis patients. Materials and Methods: 100 patients with severe chronic periodontitis (test group) and 100 periodontally healthy subjects (control group) in the age group 35-60 years participated in the study. Blood parameters were recorded with blood samples drawn from the antecubital fossa by venous puncture. Results: Periodontitis group showed lower erythrocyte count and mean corpuscular hemoglobin concentration (MCHC), and increased total leukocyte count (TLC) and neutrophil, lymphocyte, and eosinophil count, compared to the healthy control group. Conclusions: To conclude, periodontitis may tend toward anemia and there is marked leukocytosis due to increased number of circulating neutrophils and lymphocytes.